The Model of Employee Performance - Hermina, Utin Nina; Yosepha, Sri Yanthy (International Review of Management and Marketing, 2019)
The purpose of this study was to determine the leadership style, motivation, work discipline and employee performance at PT. Trakindo Utama Pontianak and the influence of leadership, motivation and work discipline styles on employee performance both simultaneously and partially. The research method used is survey research method. The type of data / information used is primary data with data collection techniques by observation, questionnaire and literature study. The research population is all employees of PT. Trakindo Utama Pontianak is 50 people. Sampling technique is census method. The analytical tool used was with the help of SPSS Data analysis techniques were carried out using path analysis approach, correlation test, determination test, simultaneous test and partial test. Findings from the results of this study are leadership style, motivation, work discipline and employee performance of PT. Trakindo Utama Pontianak is in a pretty good category, so it still needs attention, improvement and improvement. Simultaneously the influence of leadership style, motivation and work discipline has a significant effect on employee performance. Partially only work discipline has a positive and significant effect on employee performance, while leadership and motivation styles do not significantly influence employee performance, but have a positive impact on employee performance. Work discipline has the greatest influence on employee performance. Keywords: leadership style, motivation, work discipline, employee performance. JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.8025